Enhancement of Organic Solar Cell Performance through Solvent Annealing. - Kane, Derrick Michael. (Tufts Archival Research Center, 2005)
Copper phthalocyanine (CuPc) has shown promise in organic thin film electronics applications due to its ability to crystallize into ordered nanorods when exposed to solvent. In this study, CuPc nanostructured films were created through thermal evaporation of CuPc and subsequent treatment with acetone vapor for use in organic photovoltaic (OPV) cells. AFM imaging was used to confirm the growth of the nanorods, which were observed to form after 15 min of treatment and achieve a height of 50 nm after 20 min. Maximum power conversion efficiency obtained was 0.534%, a 46.5% improvement versus the untreated cell. Efficiencies achieved were significantly lower than previously reported CuPc:PCBM devices in which the acceptor layer (PCBM) was applied by solution processing (typical efficiency 1.5-3.0%). Although CuPc nanorod growth was found to increase surface roughness with increased treatment time, short circuit current density was not statistically improved. Deposition of the acceptor layer by thermal evaporation may have inadequately filled the CuPc nanostructure spacing due to 3D shadowing effects of the CuPc nanorods, and allowed the 50 nm nanorods to bridge the active layer and cause current leakage. Furthermore, the Hildebrand solubility parameter, , was studied as a useful solvent property to correlate with a solvent's effectiveness for CuPc nanorod growth. Using Fedors' group contribution method, the solubility parameter of CuPc was approximated to be 25.09 MPa1/2, with possible error due to the lack data for the copper atom. Ethanol ( = 26.0 MPa1/2) was chosen as a solvent predicted to have high CuPc solubility, compared to acetone ( = 20 MPa1/2). In case of an underestimate, dimethyl sulfoxide (DMSO) ( = 29.7 MPa1/2) was selected as upper bound. Ethanol and DMSO treatments were applied to CuPc films for 15 min. DMSO was found to raise device efficiency to 0.505%, with promising effects on fill factor and surface roughness. Advice regarding further study of DMSO treatment is included.